IKI SAE MAS AS AN INTEGRATED SOFT SKILLS CONCEPT FROM THE QUR'AN AND SUNNAH PERSPECTIVE - Aries Musnandar (State Institute of Islamic Studies (IAIN) Palu, 2018)
Best practices of formal school education, particularly in the instructional management relates to teaching and learning. Education deals with all domains of human competency. In elementary school, unfortunately, there is still a discrepancy between aim and result. Teacher misconduct will affect students’ bad character. The incorrect education process may create failure in achieving defined educational goals. It is vital for any nation to have competent educational practitioners to ensure its success in developing its students’ skills as a human capital investment of a nation. School curriculum goal is derived from the national education aims which develop students’ potentials for becoming good people in hard skills and soft skills. Therefore, the ideal teachers should understand all students’ characteristics and potentials. This research is an attempt to highlight the function of instructional management of soft skills to the success of students’ performance. The study employs a qualitative research method with multiple case study design, in which a meaning-making activity is underlined as the first objective of interpretive research in understanding social phenomena of education activities. Such phenomena to be interpreted may be found in the practical realm, skilled know-how, and experiences. Based on findings, it is known substantively that students’ soft skills will not be developed if the instructional management focuses on academic. On the other hand, soft skills will enhance significantly students’ academic results, because soft skills will enable and improve students’ potentials to reach the best learning achievement. At last, the researcher offers soft skills formula from an Islamic perspective as a comprehensive concept for building student character to be a good man. In Islamic precepts soft skills are akhlak-adab, good character, positive behavior, spread kindness and bring many benefits to others and the environment. However, these soft skills must be placed under the guidance of Qur’an and Sunnah.